KONFLIK DAN MASYARAKAT DALAM REFLEKSI HUKUM - Syofie, Syofie (Jurnal Ilmiah Penegakan Hukum, 2014)
In general overview Indonesian society is a pluralistic society, the diversitycompound. This situation is characteristic and unique identity of this country.Indonesian society is made up of various ethnic groups including ethnic Chinesein Indonesia's ethnic diversity complements culture alive and thriving today.This article provides an overview of the diversity of Indonesian society thatdiversity can be a negative impact on the integrity of the nation. This writingapproach is supported by the literature related to the law, observing thephenomena of conflict in the community, and the study of the documentationrelated data.The study found that diversity can be a strong capital for social resilience ofnational politics, but this requires considerable attention from the governmentand stakeholders, religious authority and their organization, traditional leadersand others. If the development of harmony ignored then it will cause a littlemore friction to the social conflict, the settlement if it is not resolved by thelegal umbrella is feared to affect the integrity of the Unitary Republic ofIndonesia (Republic of Indonesia).